Effects of DPP-4 inhibitors on cardiovascular outcomes in patients with type 2 diabetes and end-stage renal disease. (1st September 2016) - Chan, Shang-Yih; Ou, Shuo-Ming; Chen, Yung-Tai; Shih, Chia-Jen
Abstract: Background: Recent clinical trials have evaluated the cardiovascular outcomes of dipeptidyl peptidase-4( DPP-4) inhibitors in patients with type 2 diabetes mellitus (T2DM), but those with end-stage renal disease (ESRD) were ineligible for participation in these trials. We aimed to characterize the impact of DPP-4 inhibitors on major adverse cardiovascular events (MACEs) in patients with T2DM and ESRD undergoing chronic dialysis. Methods: This nationwide observational study utilized data from 3556 patients aged ≥ 20 years with T2DM and ESRD who initiated treatment with DPP-4 inhibitors between 1 March 2009 and 31 June 2013, retrieved from Taiwan's National Health Insurance Research Database. Each DPP-4 inhibitor user was matched to a non-user control subject using propensity scores. The primary outcomes were all-cause mortality and MACEs (ischemic stroke and myocardial infarction). The secondary outcomes were hospitalization for heart failure and hypoglycemia. All subjects were followed until death or 31 December 2013. Results: Compared with non-users, DPP-4 inhibitor users had lower risks of all-cause mortality (hazard ratio [HR] 0.43, 95% confidence interval [CI] 0.39–0.47), MACEs (HR 0.76, 95% CI 0.65–0.90), and ischemic stroke (HR 0.77, 95% CI 0.61–0.97); the risks of myocardial infarction and hospitalization for heart failure and hypoglycemia did not differ. This treatment effect remained consistent in subgroup analyses according to age, sex, comorbidities, dialysis modality, and insulin use. Conclusions: In this nationwide ESRD cohort, DPP-4 inhibitor use was associated with reduced risks of all-cause mortality and ischemic stroke. Highlights: We assessed the cardiovascular outcomes of DPP-4 inhibitors in patients with T2DM and ESRD. Use of DPP-4 inhibitor was associated with reduced risks of ischemic stroke and death. The risks of heart failure and hypoglycemia were not increased in DPP-4 inhibitor users